Cost analysis of Diabetes mellitus therapy in Dr. Sardjito Hospital Yogyakarta - Aisyah, Tri Murti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Diabetes mellitus is a chronic disorder that has been recognized by Indonesian government as a major public health problem with far reaching consequences not just for its adverse impact on the health of Indonesian, but also for the economic burden it places on the health care systems. The objective of this study was to describe the therapeutic cost of outpatient diabetes mellitus type 2.A descriptive study was performed on patient who were admitted to the Department of Endocrinology of the Sardjito Hospital between July and August 2005. Patient were included if they were ambulatory during the time of the study. Exclusion criteria were patients with any other diseases. Only direct medical cost was considered (perspective from hospital). Direct costs to this analysis were cost of drugs, visit to the physician, laboratory examinations, and cost of diabetes-related complications and concomitant therapies.From the 100 examined patients, 44 percent were females and 56 percent were males. The average age of the patients was 60.75 ranging from 41 to 85 years of age. The average total costs per patient per month was Rp 208,500 with a maximum to be Rp 754,500. The largest cost was drug acquisition costs (59.5%), followed by cost of diabetes-related complications (31%). The control of blood glucose using combination therapy was more frequently attained in patients taking sulfonylurea and biguanid (44.62%). The combination of biguanid, Î±-glucosidase inhibitor, and insulin had the greatest expense, equal to Rp.571,000. Hypertension, neuropathy, and hyperlipidemia were the most frequently mentioned complications diseases. The cost for diabetes-related complication included hypertension and retinopathy had the greatest expense, equals to Rp 754,500.Key words: cost-identification, diabetes mellitus, Dr. Sardjito hospital